Heat and mass transfer analysis of magnetohydrodynamic (MHD) thermosolutal nanofluid flow over vertical and inclined porous media - Nadab*†, H.; Amoo†, S.A.; Olopade†, I.A. (International Journal of Mathematical Analysis and Modelling, 2023)
In this study, the influence of heat and mass transfer on unsteady and steady MHD thermosolutal nanofluids flow in porous media in the presence of thermophoresis and Brownian motion effects was discussed. The governing boundary layer Partial Differential Equations (PDEs) were transformed into nonlinear Odinary Differential Equations (ODEs) by using similarity transformation and then solved numerically using fourth order Runge-Kutta method with shooting technique. It is found that increase in heat source (γ) and thermal conductivity (α) decreases the heat transfer rate but increases the skin friction and mass transfer rates. It is further discovered that the increase in thermal Grashof (Gr) and solutal Grashof (Gc) increases skin friction, heat and mass transfer rates.